2016
DOI: 10.1038/srep28461
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a Skp2-c-Myc Pathway to Expand Human Beta-cells

Abstract: Type 2 diabetes (T2D) is characterized by insulin resistance and reduced functional β-cell mass. Developmental differences, failure of adaptive expansion and loss of β-cells via β-cell death or de-differentiation have emerged as the possible causes of this reduced β-cell mass. We hypothesized that the proliferative response to mitogens of human β-cells from T2D donors is reduced, and that this might contribute to the development and progression of T2D. Here, we demonstrate that the proliferative response of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
(115 reference statements)
0
12
0
1
Order By: Relevance
“…Recent studies demonstrate that in addition to regulation of glucose-sensing transcription, MLXIP plays an important role in Myc activation and subsequent metabolic pathway reprogramming ( Carroll et al, 2015 ). It is well known that Myc has important functions in the pathogenesis of diabetes, through both regulating cell cycle entry and maintaining expansion, regeneration and normal function of beta-cells ( Tiwari et al, 2016 ). It has been shown that abnormal activation of Myc resulted in decreased beta-cell differentiation, proliferation and reduced insulin secretion ( Cheung et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrate that in addition to regulation of glucose-sensing transcription, MLXIP plays an important role in Myc activation and subsequent metabolic pathway reprogramming ( Carroll et al, 2015 ). It is well known that Myc has important functions in the pathogenesis of diabetes, through both regulating cell cycle entry and maintaining expansion, regeneration and normal function of beta-cells ( Tiwari et al, 2016 ). It has been shown that abnormal activation of Myc resulted in decreased beta-cell differentiation, proliferation and reduced insulin secretion ( Cheung et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pathological events that can lead to the development of T2D are diverse, such as deficiency and malfunction of beta-cells together with insulin resistance in multiple tissues, including liver and adipose tissues ( Tiwari et al, 2016 ). The likely underlying genes for the novel T2D signals that we identified through GWAS are key players of signaling pathways that could lead to the development of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of functional pancreatic β-cells, mainly by increased β-cell apoptosis is a central feature of both type 1 diabetes (T1D) and type 2 diabetes (T2D) [2][3][4][5]. Other possible causes of this reduced β-cell mass in diabetes include β-cell dedifferentiation [6,7] and failure of adaptive expansion due to impaired β-cell proliferation [8]. In T1D, selective β-cell destruction occurs through auto-immune-mediated processes; infiltration of activated CD 4+ /CD 8+ T cells, B cells, and macrophages in the pancreatic islets.…”
Section: Introductionmentioning
confidence: 99%
“…344 The pathological events that can lead to the development of T2D are diverse, such as deficiency 345 and malfunction of beta-cells together with insulin resistance in multiple tissues, including liver 346 and adipose tissues (Tiwari et al 2016). The likely underlying genes for the novel T2D signals 347 that we identified through GWAS are key players of signaling pathways that could lead to the 348 development of T2D.…”
mentioning
confidence: 97%